Soft skills: their influence on the productivity of a foreign trade company, 2019 - Valencia Franco, Richard Ángel (2022)
The objective of this research is to determine how interpersonal or soft skills influence the productivity of workers of the foreign trade logistics company in 2019. Competencies are the skills and abilities that an individual has to solve problems in a technological environment and interact with their peers, both within a work environment or otherwise. The latter are soft skills according to the United Nations Educational, Scientific and Cultural Organization, hereinafter (UNESCO, 2005), for its acronym in English. The research was applied, with a quantitative approach, with a non-experimental and cross-sectional correlational design. It has a sample of 268 collaborators; resulting in a Cronbach's alpha coefficient of 0.921, the Chi-Square hypothesis test of 71.961 with a level of significance α= 0.000 <0.05 and a positive and moderate Spearman correlation coefficient of 0.387, demonstrating that interpersonal or soft skills influence in the productivity of the company's workers.